Analisis Teknik Gerak Pointing Posisi Berdiri Jarak 9 Meter Pada Atlet Petanque Kabupaten Demak - Hidayati, Utami; Sulaiman (Universitas Negeri Semarang, 2024)
Petanque is a game using an iron ball where the aim is to get the ball closer to the target (boka) and with both feet in a circle (circle). The aim of this research is to analyzer the suitability and accuracy of pointing movements in a standing position at a distance of 9 meter. The method in this research uses quantitative descriptive analysis methods and data collection uses survey and documentation methods. The video recording resulys will be analyzed using kinovea software version 0.9.5. The sampling technique uses a purposive sampling technique, namely a technique for determining samples with certain considerations. This research was conducted based on data obtained from 7 petanque athletes from Demak Regency. The result showed what the average throw time was 0,48 second, the back swing angle was 57,7°- 119,5°, the release angle was 88,2°- 124,3° and the maximum ball height was 204 cm- 306,8 cm. The distance between the ball and the target is 12,1 cm- 50,8 cm, and shows that the analysis of the suitability of the standing position pointing movement is in the